Ultrawide-bandgap semiconductors: An overview - Wong, Man Hoi; Bierwagen, Oliver; Kaplar, Robert J.; Umezawa, Hitoshi (Journal of materials research, 2021)
Ultrawide-bandgap (UWBG) semiconductor technology is presently going through a renaissance exemplified by advances in material-level understanding, extensions of known concepts to new materials, novel device concepts, and new applications. This focus issue presents a timely selection of papers spanning the current state of the art in UWBG materials and applications, including both experimental results and theoretical developments. It covers broad research subtopics on UWBG bulk crystals and substrate technologies, UWBG defect science and doping, UWBG epitaxy, UWBG electronic and optoelectronic properties, and UWBG power devices and emitters. In this overview article, we consolidate the fundamentals and background of key UWBG semiconductors including aluminum gallium nitride alloys (Al x Ga 1– x N), boron nitride (BN), diamond, β -phase gallium oxide ( β -Ga 2 O 3 ), and a number of other UWBG binary and ternary oxides. Graphical Abstract